Perbandingan Model Discovery Learning dan Blended Learning Terhadap Kemampuan Pemecahan Masalah Matematis - Irfan Septiyan; Nurul Anriani; Aan Hendrayana (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2020)
ABSTRACT The purpose of this study is to examine the achievement of mathematical problem solving abilities between students who obtain learning with the discovery learning model and students who obtain learning with the blended learning model. This research is a mixed method research with concurrent embedded method. This study consisted of two experimental groups who learned by discovery learning and blended learning models. The research population is students in one of the junior high schools in Serang Regency. Banten with a class VIII research sample. Data analysis was performed quantitatively and qualitatively. Quantitative analysis is used to calculate differences in the achievement of students' mathematical problem solving abilities, while qualitative data analysis is used to strengthen the results of quantitative analysis. The results showed the percentage of achievement of students' mathematical problem solving abilities that obtained learning with the discovery learning model with students who obtained learning with the blended learning model in the medium category. There was no significant difference in the achievement of mathematical problem solving abilities between the two experimental groups. Keywords: Mathematical Problem Solving Abilities, Discovery Learnig, Blended Learn